PENGARUH LAYANAN ONLINE FOOD DELIVERY GRAB FOOD TERHADAP PERILAKU KONSUMTIF MAHASISWA YANG TINGGAL DI KOS - Ronaria Elisabeth Buaton; Anak Agung Istri Istadewanti; Ariftra Rahmawati; Ayat Tulloh Rahulloh Khomeini; Nur Aini Rakhmawati (Politeknik Ubaya, 2023)
The use of Grab Food has become widespread, including among university students. This research aims to investigate the relevance of Grab Food's services to the consumptive behavior of students living in boarding houses. The research sample consisted of 70 students who had been using Grab Food for a minimum of 6 months and were residing in boarding houses. Data analysis was conducted using quantitative descriptive and Product Moment Correlation methods. Based on the research findings, it was observed that the majority of students using Grab Food were around 20 years old, with monthly allowances ranging from Rp1.100.000 to Rp2.000.000. The average frequency of food purchases through Grab Food was three times a week. Through test soft linearity and Product Moment Correlation, it was determined that students living in boarding houses had a moderately significant relationship between their use of Grab Food services and their consumptive behavior. AA substantial departure from linearity value of 0.131 was found from the linearity test, indicating a significant linear link between consumer behavior and the habit of utilizing Grab Food services. Where as from the Product Moment Correlation test, a correlation value (r) of 0.641 was obtained, which shows that the level of relationship between the use of Grab Food services and students' consumptive behavior is at a medium level.